1991
DOI: 10.1111/j.1439-0507.1991.tb00799.x
|View full text |Cite
|
Sign up to set email alerts
|

Candidosis of the prostate: a rare form of endomycosis

Abstract: Summary. The third case of a culturally and histologically proven candidosis of the prostate in the world literature available to us is reported. Autopsy of a 59‐year‐old man with metastasizing bronchial carcinoma as predisposing primary disease revealed a local candidosis of the prostate in the left lobe of the prostate, without evidence of a Candida sepsis. Parallel and different aspects in comparison with the other two cases are described. Zusammenfassung. Der dritte Fall in der Weltliteratur einer kultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The partner’s sperm can also be colonized by the identical Candida strain found in the vagina (Mendling et al 1998), although the partner is free of symptoms. Candida prostatits is a very rare event seen only in immunosuppressed men (Golz and Mendling 1991, Sobel, Fischer and Kauffman 2010). Nonetheless, the role of the partner’s genital colonization or the orointestinal colonization of both partners as source of recurrence of recurrent Candida vaginitis is not clear (Sobel 2007).…”
Section: Genital Colonizationmentioning
confidence: 99%
“…The partner’s sperm can also be colonized by the identical Candida strain found in the vagina (Mendling et al 1998), although the partner is free of symptoms. Candida prostatits is a very rare event seen only in immunosuppressed men (Golz and Mendling 1991, Sobel, Fischer and Kauffman 2010). Nonetheless, the role of the partner’s genital colonization or the orointestinal colonization of both partners as source of recurrence of recurrent Candida vaginitis is not clear (Sobel 2007).…”
Section: Genital Colonizationmentioning
confidence: 99%
“…Many organisms have been implicated has possible sources of undocumented infection, including Mycoplasma hominis, Trichomonas vaginalis, Candida species, Ureaplasma urealyticum, Chlamydia trachomatis, herpes simplex virus, and even parasites (23)(24)(25)(26)(27)(28)(29). Such an infection may actually be an inciting incident rather than an ongoing cause that leads to development of the clinical syndrome.…”
Section: Chronic Prostatitis/chronic Pelvic Pain Syndrome (Cp/cpps)mentioning
confidence: 99%
“…However, there have been many proposed (but unsubstantiated) causes for CPPS, including infections with bacteria, viruses and yeast [11][12][13][14]. Furthermore, a casecontrolled study found no difference in the rate of positive cultures localised to expressed prostatic secretion between men with CPPS and asymptomatic men [15].…”
Section: Aetiologymentioning
confidence: 94%